Ion-Track Template Synthesis and Characterization of ZnSeO3 Nanocrystals - Dauletbekova, Alma; Akylbekova, Aiman; Sarsekhan, Gulnaz; Usseinov, Abay; Baimukhanov, Zein; Kozlovskiy, Artem; Vlasukova, Liudmila A.; Komarov, Fadey F.; Popov, Anatoli i.; Akilbekov, Abdirash T. (MDPI, 2022)
ZnSeO3 nanocrystals with an orthorhombic structure were synthesized by electrochemical and chemical deposition into SiO2/Si ion-track template formed by 200 MeV Xe ion irradiation with the fluence of 107 ions/cm2 . The lattice parameters determined by the X-ray diffraction and calculated by the CRYSTAL computer program package are very close to each other. It was found that ZnSeO3 has a direct band gap of 3.8 eV at the Γ-point. The photoluminescence excited by photons at 300 nm has a low intensity, arising mainly due to zinc and oxygen vacancies. Photoluminescence excited by photons with a wavelength of 300 nm has a very low intensity, presumably due to electronic transitions of zinc and oxygen vacancies. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.
A.I.P. thanks the Institute of Solid-State Physics, University of Latvia. ISSP UL as the Center of Excellence is supported through the Framework Program for European universities. The work was carried out within the framework of the grant AP05134367 of the Ministry Funding: The work was carried out within the framework of the grant AP05134367 of the Ministry of education and Science Science of of the Republic Republic of Kazakhstan.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; chemical and electrochemical deposition; quantum chemical calculation; SiO2/Si track template; XRD study; ZnSeO3 nanocrystals